Planteamiento metodológico para el diagnóstico del banco de reactores de la planta piloto de la Fundación Universidad de América bajo las condiciones de diseño y operación establecidas por el fabricante (2019)
The title of the project presented in this document is "Planteamiento metodológico para el diagnóstico del banco de reactores de la planta piloto de la Fundación Universidad de America bajo las condiciones de diseño y operación entregadas por el fabricante". in the first chapter, corresponding to the general aspects of the project, it tackles scale-up of chemical industrial processes, principles of chemical reactors design, and basic mechanisms of corrosion. In the second chapter was carried out a technical and operational characterization of the devices and units of the pilot plant reactors based on the document "Manual de operación del banco de reactores" made by the fabricator. It was made a chemical reaction selection taking into account the chemical resistance of the construction material resulting in the alkaline hydrolysis of ethyl acetate, the acetic anhydride hydrolysis, the alkaline decomposition of diacetone alcohol, and the esterification of acetic acid with ethanol using methanesulfonic acid as catalyst. In the third chapter it was developed a mathematical model for the alkaline hydrolysis of ethyl acetate simulation in the pilot plant reactors taking into account four reactors configuration, solving the mathematical model numerically and comparing with the simulation results in Aspen Plus. The results were consistent, and the mathematical model and simulation can be extended for different conditions. Finally, it was made the pilot plant reactors laboratory guide for teaching.